Exploitation of wasted bread as substrate for polyhydroxyalkanoates production through the use of Haloferax mediterranei and seawater - Montemurro, Marco; Salvatori, Gaia; Alfano, Sara; Martinelli, Andrea; Verni, Michela; Pontonio, Erica; Villano, Marianna; Rizzello, Carlo Giuseppe (Frontiers in Microbiology, 2022)
The use of the halophile microorganism Haloferax mediterranei, able to synthesize poly(hydroxybutyrate-hydroxyvalerate) (PHBV), is considered as a promising tool for the industrial production of bioplastic through bioprocessing. A consistent supplementation of the growth substrate in carbohydrates and minerals is overall necessary to allow its PHBV production. In this work, wasted bread was used as substrate for bioplastic production by microbial fermentation. Instead of the consistent and expensive minerals supplement required for Hfx. mediterranei DSM1411 growth, microfiltered seawater was added to the wasted bread-derived substrate. The suitable ratio of wasted bread homogenate and seawater, corresponding to 40:60, was selected. The addition of proteases and amylase to the bread homogenate promoted the microbial growth but it did not correspond to the increase of bioplastic production by the microorganism, that reach, under the experimental conditions, 1.53 g/L. An extraction procedure of the PHBV from cells, based on repeated washing with water, followed or not by a purification through ethanol precipitation, was applied instead of the conventional extraction with chloroform. Yield of PHBV obtained using the different extraction methods were 21.6 ± 3.6 (standard extraction/purification procedure with CHCl3:H2O mixture), 24.8 ± 3.0 (water-based extraction), and 19.8 ± 3.3 mg PHAs/g of wasted bread (water-based extraction followed by ethanol purification). Slightly higher hydroxyvalerate content (12.95 vs 10.78%, w/w) was found in PHBV obtained through the water-based extraction compared to the conventional one, moreover, the former was characterized by purity of 100% (w/w). Results demonstrated the suitability of wasted bread, supplemented with seawater, to be used as substrate for bioplastic production through fermentation. Results moreover demonstrated that a solvent-free extraction, exclusively based on osmotic shock, could be used to recover the bioplastic from cells.